Fostering Mathematical Creativity by Teaching Logically Precisely Reasoning at the Grade Two - Grabauskienė, Vaiva; Mockaitytė-Rastenienė, Oksana (Pedagogika, 2016)
In this article, the teaching of mathematical reasoning in the primary school is being analysed through the scope of mathematical creativity and their interconnections are being explained in more detail. Also, a construct of mathematical creativity is being defined. The logic of an empirical research is based on an idea that the lack of knowledge in mathematical syntax and, especially, incomprehension of semantic suppress the mathematical creativity. Wherefore, an analysis of content and number of children mistakes may let observe how the learning environment influences mathematical creativity. Methods: written survey, classical teaching experiment, content analysis. For the teaching of mathematical reasoning, the original purposefully created system of mathematical activities was used, based on a principle concrete-pictorial-abstract. The total number of researching type exercises done by children in an experimental class was thirteen, and the exercises were from different fields of mathematics. The previously mentioned method of teaching mathematics resulted in decrease in overall mistakes done by the children and it reached a one third. The changes in proportion between syntax and semantic mistakes were evident. After the experiment, the experimental class made as half as less semantic mistakes, in comparison to the control class. This indicated that learning by researching promoted mathematical creativity in children.